2013
DOI: 10.1051/0004-6361/201321636
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion irradiation of water ice from MeV to GeV energies

Abstract: Context. Cosmic ray ion irradiation affects the chemical composition of and triggers physical changes in interstellar ice mantles in space. One of the primary structural changes induced is the loss of porosity, and the mantles evolve toward a more compact amorphous state. Previously, ice compaction was monitored at low to moderate ion energies. The existence of a compaction threshold in stopping power has been suggested. Aims. In this article we experimentally study the effect of heavy ion irradiation at energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 46 publications
1
71
0
Order By: Relevance
“…Nevertheless, as mentioned in Sect. 1, these ions are expected to be an important component of cosmic rays in space; in the past five years several experiments simulated their effects in various molecular ice components (Seperuelo Duarte et al 2009Pilling et al 2010a,b;Dartois et al 2013). We conclude that in our selected ice mixture where both components, methanol and ammonia, are dissociated easily by vacuum-UV photons, similar photon and ion energy doses led to similar chemical reactions, based on the similarity of the IR spectra of the processed ices.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as mentioned in Sect. 1, these ions are expected to be an important component of cosmic rays in space; in the past five years several experiments simulated their effects in various molecular ice components (Seperuelo Duarte et al 2009Pilling et al 2010a,b;Dartois et al 2013). We conclude that in our selected ice mixture where both components, methanol and ammonia, are dissociated easily by vacuum-UV photons, similar photon and ion energy doses led to similar chemical reactions, based on the similarity of the IR spectra of the processed ices.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
“…The results obtained in these experiments were often extrapolated to higher energies (on the order of 1 GeV) for astrophysical ices. In recent years, some experiments have reached energies near 1 GeV (Seperuelo Duarte et al 2009Pilling et al 2010a,b;Dartois et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy of a water molecule increases with its number of neighbours and is estimated at 0.22 eV per hydrogen bond (Brill & Tippe 1967;Isaacs et al 1999;Dartois et al 2013). In fact, the hydrogen bond strength depends on the number of water molecules involved as donors and acceptors in the neighbourhood (Huš & Urbic 2012).…”
Section: Mobility Of Water Molecules Within the Icementioning
confidence: 99%
“…We report on calculations performed with dE/dx powers α = 1 and α = 2. For bulk modifications, such as dehydrogenation of carbonaceous material (Godard et al 2011), or ice compaction (Dartois et al 2013), the slope α has been found close to unity in experiments. For desorption processes (i.e.…”
Section: Structural Modification and Desorption From Large Grainsmentioning
confidence: 65%